2004
DOI: 10.4028/www.scientific.net/kem.261-263.1605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Nano-Crystallization on Microstructure and Mechanic Properties of Commercial Pure Titanium

Abstract: The paper investigated nano-crystallization on surface layer of commercial pure titanium by using high-energy shot peening. The grain size and the microstructure in deformed surface layer by high-energy shot peening are analyzed with X-ray diffraction and TEM etc. In addition, the variations of surface microhardness are examined after high-energy shot peening. The results described that the nano-crystalline surface layer have been formed in commercial pure titanium with a structure of hexagonal closet packet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…For commercial pure titanium, there were few reports to improve fatigue limit by high-energy shot peening (HESP). In the earlier stage, Authors have researched surface nanocrystallization on commercial pure titanium by high-energy shot peening [7,8] and improvement of its fatigue limit by high-energy shot peening [9]. The results indicated that the highenergy shot peening is more effective way to improve fatigue limit of commercial pure titanium, due to both formation of surface nanocrystalline layer and work-hardening by the high-energy shot peening; the influencing factors of surface damage, roughness, and edge of specimen etc, did harms to fatigue limit of commercial pure titanium, and even cause the function of nano-grained layer to be counteracted.…”
Section: Introductionmentioning
confidence: 99%
“…For commercial pure titanium, there were few reports to improve fatigue limit by high-energy shot peening (HESP). In the earlier stage, Authors have researched surface nanocrystallization on commercial pure titanium by high-energy shot peening [7,8] and improvement of its fatigue limit by high-energy shot peening [9]. The results indicated that the highenergy shot peening is more effective way to improve fatigue limit of commercial pure titanium, due to both formation of surface nanocrystalline layer and work-hardening by the high-energy shot peening; the influencing factors of surface damage, roughness, and edge of specimen etc, did harms to fatigue limit of commercial pure titanium, and even cause the function of nano-grained layer to be counteracted.…”
Section: Introductionmentioning
confidence: 99%
“…Shot peening is an essential process of work-hardening which will induce high CRS, refined domain sizes and high density of dislocations. Furthermore, some study showed [31] that nano-crystalline layer can be formed after shot peening, and the nano-crystalline layer has much higher microhardness because of higher dislocation density. In the process of stress shot peening, the materials are in the stress state directly after peening but before unloading, subsequently, after unloading the prestress, elastic deformation induced by tensile stress loaded before shot peening is recovered, which introduces higher CRS and more severe deformation layer.…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…One of the surface treatment methods that have a positive effect on fatigue life is shot peening, which consists of increasing the strength of a surface layer of material by bombarding it with a stream of metal shot. Shot peening is used for treating machine components made of titanium alloys [24][25][26][27][28]. The application of shot peening leads to increased fatigue life of a jet engine compressor disc made of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Increased fatigue life due to the application of vibratory shot peening was also observed for Ti6Al4V titanium alloy [26]. Wen et al [28] investigated nano-crystallization on the surface layer of commercial pure titanium using high-energy shot peening.…”
Section: Introductionmentioning
confidence: 99%